Murder made her wicked - Hobbs, Elizabeth (Mystery writer) (Hobbs, Elizabeth (Mystery writer). Marigold Manners mystery., 2025)
Penniless Boston heiress and accomplished modern woman Marigold Manners has put her past to good use, selling the story of the Great Misery Island Murders to earn enough money to resume the life she was always meant to have and return to her studies at Wellesley College. But her carefully laid plans for academic excellence are thrown into disarray when she stumbles across the body of a young woman in the campus lake. When the peace of the bucolic campus is shattered by the murder, the cloistered world of a women's college that Marigold finds so comforting proves it is not immune to the malice and wickedness of the world. The closed community becomes a hothouse where disparagement blooms into insult and small slights that have festered for years blossom into academic rivalries that could spill over into something far more sinister. Marigold must use every ounce of her logic and enlist her eccentric, colorful cast of fellow students and found family to identify the girl and find the murderer-before they kill again--Publisher's description.